Elasto-plastic model to determine the maximum force for shaft straightening process (2017)
This paper shows the development of a mathematical model based on elasto-plastic behavior of materials in order to determine the bending moment and the maximum straightening force required to repair a bent shaft. The importance of this work is because many machines use shafts to transmit power and movement, and these elements can suffer permanent deflections during operation cycles. An appropriate reparation process can increase the life of these elements significantly. Knowing the mechanics for a straightening process is essential for design, processes and maintenance engineers in charge of systems that use these elements (shafts).